How schools can help students recover from traumatic experiences : a tool-kit for supporting long-term recovery - Jaycox, Lisa (Technical report (Rand Corporation), 2006)
"Many changes in students' performance and behavior stem from the emotional and behavioral problems that they may experience following such traumas as witnessing violence, undergoing assault or abuse, living through natural disasters, or experiencing acts of terrorism. This paper groups the programs to help support the long-term recovery of traumatized students according to the kinds of trauma they address, and describes how to select students for a program. Finally, it gives a one-page summation of each program selected. This summation describes the objective, intended population, and format of the program and provides details on implementation, personnel training and materials, and contact information."--Source other than the Library of Congress